A preparation process of a neodymium-iron-boron magnet with gallium-cobalt dual-element regulation of inorganic fluoride grain boundary diffusion

CN122658873APending Publication Date: 2026-08-28HUNAN BENLANG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611101031.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0005]有鉴于此,本发明的目的在于提出一种镓钴双元素调控无机氟化物晶界扩散的钕铁硼磁体制备工艺,以解决现有无机氟化物晶界扩散中,扩散源促渗透和高温稳定化作用难以按时序受控发挥,导致矫顽力提升、剩磁保持与热稳定性难以同时兼顾的问题

Benefits of technology

本发明将无机氟化物粉体先与镓源在无水体系中进行接触分散,使镓源优先接近氟化物粉体表面,形成具有Ga-F界面固定特征的中间浆料。该设置有利于把镓的促渗透作用限制在晶界反应入口附近,降低普通物理混合中游离镓提前迁移或表层液相局部富集的风险,从而为烧结钕铁硼稀土永磁材料提供较连续的晶界扩散通道。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to sintered Nd-Fe-B rare earth permanent magnet material technical field, specifically to a kind of preparation process of gallium cobalt double-element regulated inorganic fluoride grain boundary diffusion neodymium-iron-boron magnet.The process will be pretreated sintered Nd-Fe-B magnet as matrix, inorganic fluoride powder and gallium source are first ball milled in anhydrous system, form Ga-F interface fixed intermediate slurry;Then add cobalt source and cooperate into film agent, dispersing agent to obtain sequential fixed type composite diffusion source slurry, after coating on the surface of magnet, by low-temperature oxygen-free pre-conversion, grain boundary main diffusion and segmented tempering to obtain modified magnet.The present application is conducive to control the contact sequence and migration state of gallium and cobalt in diffusion source particles, so that neodymium-iron-boron rare earth permanent magnet material can improve intrinsic coercivity while maintaining good remanence, demagnetization curve squareness and high temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sintered NdFeB rare earth permanent magnet materials, and particularly to a process for preparing NdFeB magnets by controlling the diffusion of inorganic fluoride grain boundaries using gallium and cobalt dual elements. Background Technology

[0002] Sintered NdFeB magnets are typical rare-earth permanent magnet materials with high energy product, and are widely used in high-temperature, high-load motors and magnetic functional components. As service temperatures and demagnetization resistance requirements increase, simply increasing the heavy rare-earth content to improve coercivity can easily increase raw material costs and reduce remanence. Therefore, grain boundary diffusion has become an important process for improving the high-temperature stability of NdFeB magnets.

[0003] Existing grain boundary diffusion processes typically involve applying rare earth fluorides, oxides, or diffusion sources containing low-melting-point metals to the magnet surface, followed by high-temperature diffusion and tempering to allow the diffusing elements to penetrate the magnet along the grain boundaries. While this method can improve coercivity to some extent, the diffusion sources often exist in a physically mixed or single-load state, making it difficult to control the contact sequence and interface state between the powder and the penetration-enhancing and stabilizing components.

[0004] In inorganic fluoride grain boundary diffusion systems, if the pro-permeation phase accumulates too early on the surface, it can easily lead to discontinuous supply of grain boundary inlets. Furthermore, if the stabilizing elements are unevenly distributed at high temperatures, it may affect the squareness of the demagnetization curve and thermal stability. Therefore, how to achieve more controlled interfacial contact and diffusion sequence at the grain boundary diffusion source of rare-earth permanent magnet materials under conditions of low or no heavy rare-earth content remains to be improved. Summary of the Invention

[0005] In view of this, the purpose of this invention is to propose a gallium-cobalt dual-element controlled inorganic fluoride grain boundary diffusion process for the preparation of NdFeB magnets, in order to solve the problem that in the existing inorganic fluoride grain boundary diffusion, the diffusion source's infiltration-promoting and high-temperature stabilization effects are difficult to be controlled in a timely manner, resulting in the difficulty in simultaneously achieving coercivity improvement, remanence retention and thermal stability.

[0006] To achieve the above objectives, this invention provides a process for preparing NdFeB magnets by controlling inorganic fluoride grain boundary diffusion using gallium-cobalt dual elements, comprising the following steps: S1. Perform surface pretreatment on sintered NdFeB magnets to obtain pretreated magnets; S2. Mix anhydrous neodymium fluoride powder and anhydrous praseodymium fluoride powder and dehydrate to obtain dehydrated inorganic fluoride powder; wherein the dehydrated inorganic fluoride powder is composed of 60-75wt% anhydrous neodymium fluoride powder and 25-40wt% anhydrous praseodymium fluoride powder. S3. Add gallium triacetylacetonate, anhydrous ethanol and ethyl acetate to the dehumidified inorganic fluoride powder obtained in step S2, and ball mill in an anhydrous system to obtain Ga-F interface-fixed intermediate slurry; the particle D50 of the Ga-F interface-fixed intermediate slurry is 0.55-0.90 μm; S4. Disperse anhydrous cobalt(II) acetylacetone in ethyl acetate to obtain a cobalt source dispersion. After step S3, add the cobalt source dispersion to the Ga-F interface fixation intermediate slurry and control the Co / Ga molar ratio to be 0.35-0.65. After dispersion, a cobalt source post-confinement composite slurry is obtained. S5. Add polyvinyl butyral film-forming agent and non-aqueous polycarboxylate dispersant to the cobalt source confinement composite slurry obtained in step S4 to obtain a sequentially fixed composite diffusion source slurry. Coat the sequentially fixed composite diffusion source slurry onto the surface of the pretreated magnet obtained in step S1 and dry it to obtain a coated magnet. S6. Place the coated magnet obtained in step S5 in an inert atmosphere, first heat it at 210-240℃ for 25-45 min for oxygen-free pre-conversion before main diffusion, then heat it at 820-850℃ for 130-170 min for main grain boundary diffusion, and then perform segmented tempering to obtain a neodymium iron boron magnet modified by inorganic fluoride grain boundary diffusion regulated by gallium and cobalt dual elements.

[0007] Preferably, in step S1, the sintered NdFeB magnet is an N48SH grade sintered NdFeB magnet; the surface pretreatment includes: lightly grinding the magnet surface to a surface roughness Ra of 0.6 μm, ultrasonically cleaning it in acetone and anhydrous ethanol for 3 min in sequence, and drying it at 80°C and 100 Pa for 20 min.

[0008] Preferably, in step S2, the anhydrous neodymium fluoride powder and anhydrous praseodymium fluoride powder are dried at 120°C and 80 Pa for 2 hours, and then transferred to a ball mill container protected by dry argon gas after cooling.

[0009] Preferably, in step S3, for every 12 parts by mass of the dehydrated inorganic fluoride powder, 0.82-1.10 parts by mass of gallium triacetylacetonate, 24 parts by mass of anhydrous ethanol, 12 parts by mass of ethyl acetate and 60 parts by mass of zirconium oxide beads are added, and the mixture is ball-milled at 350 r / min for 1.4-3 h at 28 °C.

[0010] Preferably, in step S4, for every 12 parts by mass of the dehydrated inorganic fluoride powder, 0.233-0.433 parts by mass of anhydrous cobalt(II) acetylacetonate are added.

[0011] Preferably, in step S4, the cobalt source dispersion is added to the Ga-F interface fixation intermediate slurry within 5 minutes, and the stirring speed is maintained at 280 r / min during the addition. After the addition is completed, the dispersion continues for 40 minutes.

[0012] Preferably, in step S5, the polyvinyl butyral film-forming agent is a 5.0% polyvinyl butyral solution, and the solvent of the polyvinyl butyral solution is composed of anhydrous ethanol and ethyl acetate in a mass ratio of 1:1; the solid content of the sequentially fixed composite diffusion source slurry is 21.3-21.8 wt%.

[0013] Preferably, in step S5, the coating process includes: immersing the pretreated magnet in the sequentially fixed composite diffusion source slurry for 10 seconds at 25°C and 40% relative humidity, then removing it at 50 mm / min and allowing it to stand for 60 seconds; after drying, controlling the dry weight gain to be 3.75-3.85 mg / cm² based on the surface area of ​​the pretreated magnet. 2 .

[0014] Preferably, in step S6, when performing the oxygen-free pre-conversion before the main diffusion, the oxygen content in the furnace is not higher than 30 ppm and the dew point is not higher than -45°C; the segmented tempering includes: after the main diffusion of the grain boundary is completed, cooling to 540°C and holding for 150 min, then cooling to 430°C and holding for 210 min.

[0015] The beneficial effects of this invention are: This invention involves first dispersing inorganic fluoride powder with a gallium source in an anhydrous system, allowing the gallium source to preferentially approach the surface of the fluoride powder, forming an intermediate slurry with Ga-F interface fixation characteristics. This arrangement helps to confine the gallium-promoting permeation effect to the vicinity of the grain boundary reaction inlet, reducing the risk of premature migration of free gallium or local enrichment of the surface liquid phase in ordinary physical mixing, thereby providing a more continuous grain boundary diffusion channel for sintering NdFeB rare earth permanent magnet materials.

[0016] After the intermediate slurry is fixed at the Ga-F interface, the cobalt source is added, and the dispersion and Co / Ga ratio in the later stages are controlled to prevent the cobalt source from competing for interface positions with the gallium source and inorganic fluoride powder during the initial ball milling stage. This sequential fixing method is beneficial for cobalt to participate in diffusion modification in a confined state in the later stages, reducing the interference of premature cobalt-enriched phase formation on the penetration-promoting process, and helping the diffused grain boundary phase to maintain a relatively stable state under high-temperature service conditions.

[0017] This invention further enhances the diffusion uniformity of composite diffusion source particles by controlling particle size, coating the film-forming carrier, and performing oxygen-free pre-conversion before main diffusion. This ensures that the particles undergo devolatilization and interface pre-fixation before entering high-temperature grain boundary diffusion, reducing the impact of concentrated volatilization, oxidation, and particle agglomeration on diffusion uniformity during the main diffusion stage. After grain boundary main diffusion and segmented tempering, the magnet can maintain remanence and maximum energy product within a relatively stable range while improving intrinsic coercivity, and also improves the squareness of the demagnetization curve, high-temperature magnetic flux retention, and wet-heat weight loss performance. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0019] Raw material source: Sintered NdFeB magnet blanks: sourced from Zhejiang Yingluohua Magnetics Co., Ltd., model N48SH grade sintered NdFeB magnets, with an intrinsic coercivity of not less than 1592kA / m; Polyvinyl butyral: sourced from Kuraray, model number Mowital B30H Non-aqueous polycarboxylate dispersant: sourced from BYK Corporation, model number BYK-W 961.

[0020] Example 1: (1) Take 20 N48SH grade sintered NdFeB magnets, each with a size of 10mm×10mm×5mm. Lightly grind each surface of the magnet with 800-grit sandpaper to control the surface roughness Ra to 0.6μm; then place the magnets in acetone and anhydrous ethanol in sequence for ultrasonic cleaning for 3min, and dry them at 80℃ and 100Pa for 20min to obtain pretreated magnets; (2) Take 8.4g of anhydrous neodymium fluoride powder and 3.6g of anhydrous praseodymium fluoride powder, mix them and dry them at 120℃ and 80Pa for 2h. After cooling to room temperature, transfer them to a zirconia ball mill jar protected by dry argon gas to obtain dehumidified inorganic fluoride powder. (3) Add 0.95g of gallium triacetylacetonate, 24g of anhydrous ethanol, 12g of ethyl acetate and 60g of zirconia beads with a diameter of 0.5mm to a zirconia ball milling jar containing the dehydrated inorganic fluoride powder. After sealing, ball mill at 350r / min for 2h at 28℃ to obtain Ga-F interface fixed intermediate slurry. The particle D50 of the Ga-F interface fixed intermediate slurry was measured to be 0.70μm. (4) Take 0.333 g of anhydrous cobalt(II) acetylacetone and add it to 5 g of ethyl acetate and stir to disperse to obtain a cobalt source dispersion. Add the cobalt source dispersion to the Ga-F interface fixation intermediate slurry obtained in step (3) within 5 min, and keep the stirring speed at 280 r / min during the addition; after the addition is complete, continue to disperse for 40 min to obtain the cobalt source confined composite slurry. (5) Add 10g of a 5.0% polyvinyl butyral solution and 0.08g of a non-aqueous polycarboxylate dispersant to the cobalt source confined composite slurry obtained in step (4). The solvent of the polyvinyl butyral solution is composed of anhydrous ethanol and ethyl acetate in a mass ratio of 1:1. After stirring for 10 minutes, separate the zirconia beads with a 100-mesh sieve and collect the sequentially fixed composite diffusion source slurry. The solid content of the sequentially fixed composite diffusion source slurry is 21.5 wt%. (6) Under the conditions of 25℃ and 40% relative humidity, the pretreated magnet obtained in step (1) is immersed in the sequential fixed composite diffusion source slurry obtained in step (5) for 10s, lifted out at 50mm / min and left to stand for 60s; weighed immediately after being removed from the tank, and the wet liquid volume of each magnet is controlled to be 70.6mg. The coated magnet is dried at 80℃ and 100Pa for 30min, and the dry weight gain of each magnet is controlled to be 15.2mg, and the total dry weight gain of 20 magnets is 304mg; the remaining slurry in the coating tank and the slurry adhering to the wall of the container are not included in the dry weight gain, and the coated magnet with sequential fixed composite diffusion source particles on the surface is obtained; (7) Place the coated magnet obtained in step (6) in an argon-protected furnace, and control the oxygen content in the furnace to be 30 ppm and the dew point to be -45℃. Heat to 220℃ at 3℃ / min and hold for 35 min to complete the oxygen-free pre-conversion before the main diffusion; then heat to 830℃ at 5℃ / min and hold for 150 min to carry out the main diffusion of the grain boundary; after the main diffusion is completed, cool down to 540℃ with the furnace and hold for 150 min, then cool down to 430℃ and hold for 210 min, and cool to room temperature to obtain the neodymium iron boron magnet modified by inorganic fluoride grain boundary diffusion regulated by gallium and cobalt.

[0021] Example 2: The difference between Example 2 and Example 1 is as follows: In step (2), 7.2g of anhydrous neodymium fluoride powder and 4.8g of anhydrous praseodymium fluoride powder were taken; in step (3), 0.82g of gallium triacetylacetonate was added, and the ball milling time was adjusted to 3h. The particle D50 in the Ga-F interface fixed intermediate slurry was measured to be 0.55μm; in step (4), the amount of anhydrous cobalt(II) acetylacetonate was adjusted to 0.287g, and the Co / Ga ratio was 0.50; in step (5), the solid content of the sequential fixed composite diffusion source slurry was 21.3wt%; in step (6), the wet liquid volume of each magnet was controlled to be 70.4mg, and the dry weight gain of each magnet was 15.0mg; in step (7), the oxygen-free pre-conversion condition was adjusted to 210℃ for 45min, and the grain boundary main diffusion condition was adjusted to 820℃ for 170min; the other conditions were the same as in Example 1.

[0022] Example 3: The difference between Example 3 and Example 1 is as follows: in step (2), 9.0g of anhydrous neodymium fluoride powder and 3.0g of anhydrous praseodymium fluoride powder are taken; in step (3), 1.10g of gallium triacetylacetonate is added, and the ball milling time is adjusted to 1.4h. The particle D50 in the Ga-F interface fixed intermediate slurry is measured to be 0.90μm; in step (4), the amount of anhydrous cobalt(II) acetylacetonate is adjusted to 0.385g, and the Co / Ga ratio is 0.50; in step (5), the solid content of the sequential fixed composite diffusion source slurry is 21.8wt%; in step (6), the wet liquid volume of each magnet is controlled to be 70.6mg, and the dry weight gain of each magnet is 15.4mg; in step (7), the oxygen-free pre-conversion condition is adjusted to 240℃ for 25min, and the grain boundary main diffusion condition is adjusted to 850℃ for 130min; the other conditions are the same as in Example 1.

[0023] Example 4: The difference between Example 4 and Example 1 is that: in step (4), the amount of anhydrous cobalt(II) acetylacetonate is adjusted to 0.233g and the Co / Ga ratio is 0.35; the solid content of the sequential fixed composite diffusion source slurry obtained in step (5) is 21.4wt%; in step (6), the wet liquid volume of each magnet is controlled to be 70.1mg and the dry weight gain of each magnet is 15.0mg; the other conditions are the same as in Example 1.

[0024] Example 5: The difference between Example 5 and Example 1 is that: in step (4), the amount of anhydrous cobalt(II) acetylacetonate is adjusted to 0.433g and the Co / Ga ratio is 0.65; the solid content of the sequential fixed composite diffusion source slurry obtained in step (5) is 21.7wt%; in step (6), the wet liquid volume of each magnet is controlled to be 70.5mg and the dry weight gain of each magnet is 15.3mg; the other conditions are the same as in Example 1.

[0025] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that steps (2) to (6) are omitted, and the pretreated magnet obtained in step (1) is directly processed according to the heating, main diffusion and tempering conditions in step (7), while the other conditions are the same as in Example 1.

[0026] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that: gallium triacetylacetonate is not added in step (3), and anhydrous cobalt(II) acetylacetonate is not added in step (4). Inorganic fluoride diffusion source slurry is prepared only from the dehumidified inorganic fluoride powder obtained in step (2). After ball milling for 2 hours, the particle D50 is measured to be 0.72 μm. In step (6), the dry weight gain of each magnet is controlled to be 15.1 mg. The other conditions are the same as in Example 1.

[0027] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in step (3), 0.95g of gallium triacetylacetonate and 0.333g of anhydrous cobalt(II) acetylacetonate were simultaneously added to a zirconium oxide ball mill jar containing the dehumidified inorganic fluoride powder for ball milling, and the cobalt source addition operation in step (4) was no longer performed; after ball milling, the particle D50 was measured to be 0.70μm, and the other conditions were the same as in Example 1.

[0028] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that: in step (3), gallium triacetylacetonate is not added, and the dehumidified inorganic fluoride powder is first ball-milled with anhydrous ethanol, ethyl acetate and zirconium oxide beads for 2 hours, and the particle D50 is measured to be 0.71 μm; in step (4), 0.333 g of anhydrous cobalt(II) acetylacetonate is still added, and the other conditions are the same as in Example 1.

[0029] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that: no anhydrous cobalt(II) acetylacetone is added in step (4), and the Ga-F interface fixation intermediate slurry obtained in step (3) is directly fed into step (5) to prepare the diffusion source slurry. The particle D50 is measured to be 0.69 μm. The other conditions are the same as in Example 1.

[0030] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that the ball milling time in step (3) was adjusted to 5h, and the particle D50 in the Ga-F interface fixed intermediate slurry was measured to be 0.35μm. The other conditions were the same as in Example 1.

[0031] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is that the ball milling time in step (3) was adjusted to 0.5h, and the particle D50 in the Ga-F interface fixed intermediate slurry was measured to be 1.25μm. The other conditions were the same as in Example 1.

[0032] Comparative Example 8: The difference between Comparative Example 8 and Example 1 is that the 220°C oxygen-free pre-conversion step is omitted in step (7), and the coated magnet obtained in step (6) is directly heated to 830°C at 5°C / min and held for 150min for grain boundary main diffusion. The other conditions are the same as in Example 1.

[0033] Performance testing: (1) Magnetic performance test: conducted according to GB / T 3217-2013. The sample size was 10mm×10mm×5mm, the magnetization direction was 5mm thickness, and the test temperature was 23℃±2℃. Five samples were taken from each group for testing and the average value was taken. Hcj0 and Br0 are the test values ​​of the pretreated magnet before coating, and Hcj1 and Br1 are the test values ​​of the magnet after diffusion modification; ΔHcj=Hcj1-Hcj0, Br change=Br1-Br0. (BH)max was read from the demagnetization curve, and the squareness of the demagnetization curve was evaluated by Hk / Hcj, where Hk is the reverse magnetic field strength corresponding to the magnetic polarization intensity dropping to 0.9Br.

[0034] (2) High-temperature irreversible magnetic flux loss test: conducted according to GB / T 40794-2021. First, the open-circuit magnetic flux Φ0 of the sample was measured at 23℃±2℃. Then, the sample was placed in an environment of 150℃ for 2 hours and cooled to 23℃±2℃ to measure the open-circuit magnetic flux Φ1. High-temperature irreversible magnetic flux loss = (Φ0-Φ1) / Φ0×100%. Five samples were taken from each group for testing and the average value was taken.

[0035] (3) Weight loss test: conducted according to GB / T 40792-2021. The surface area S of each sample is 4.00 cm². 2 Before the test, the mass m0 of the sample was measured. The sample was then placed in a 120℃, 0.20MPa water vapor environment for 96 hours, cooled, dried, and weighed again to obtain the mass m1. The weight loss was calculated as (m0 - m1) × 1000 / s, in mg / cm³. 2 Five samples were taken from each group for testing, and the average value was calculated.

[0036] (4) Particle size test: The particle size distribution of the Ga-F interface fixed intermediate slurry or corresponding diffusion source slurry was determined by laser diffraction according to GB / T 20170.1-2006, and the D50 was read.

[0037] Table 1. Magnetic property test results of each sample

[0038] Table 2. Results of high-temperature magnetic flux irreversible loss and weight loss tests for each sample.

[0039] As shown in Table 1, after grain boundary diffusion modification in Examples 1-5, Hcj1 was 1998-2108 kA / m, an increase of 357-466 kA / m compared to the magnets before the corresponding treatment; at the same time, Br change was controlled within -0.015T to -0.008T, and (BH)max remained at 367.4-373.9 kJ / m. 3The above results indicate that, under the specified diffusion source composition, D50, Co / Ga, and heat treatment conditions, the intrinsic coercivity of the magnet can be improved, while the remanence and maximum energy product remain within a relatively stable range.

[0040] Hk / Hcj was used to evaluate the squareness of the demagnetization curve. The Hk / Hcj of Examples 1-5 was 0.936-0.958, which was higher than that of Comparative Examples 1-8 (0.900-0.928). Combined with the results of irreversible high-temperature magnetic flux loss in Table 2, the irreversible high-temperature magnetic flux loss of Examples 1-5 was 1.41-2.10%, which was lower than that of Comparative Examples 1-8 (3.82-6.20%). This indicates that the sequentially prepared composite diffusion source and the oxygen-free pre-conversion before the main diffusion are beneficial for obtaining a more stable diffusion-modified state.

[0041] Comparative Examples 1 and 2 correspond to blank heat treatment and inorganic fluoride diffusion alone, respectively, with Hcj increases of 15 kA / m and 195 kA / m, lower than Examples 1-5. In Comparative Example 3, Ga and Co sources were added simultaneously during ball milling, resulting in an Hk / Hcj ratio of 0.904 and a high-temperature irreversible flux loss of 4.51%. Comparative Examples 4 and 5 lacked either a Ga or Co source, and their Hcj1 and high-temperature irreversible flux loss did not reach the levels of the examples. The above data indicate that the pre-contact treatment of the gallium source with the inorganic fluoride powder and the subsequent addition of the cobalt source both affect the final magnetic properties and thermal stability.

[0042] Comparative Examples 6 and 7 had their D50 adjusted to 0.35 μm and 1.25 μm, respectively, with Hcj1 values ​​of 1956 kA / m and 1868 kA / m, lower than those of Examples 2 and 3, where D50 was 0.55-0.90 μm. In Comparative Example 8, omitting the 220°C oxygen-free pre-conversion, the irreversible high-temperature magnetic flux loss increased to 5.11%, with a weight loss of 1.50 mg / cm³. 2 The values ​​were all higher than in Example 1. This indicates that the particle size of the diffusion source particles and the pre-conversion treatment before main diffusion jointly affect the retention of magnetic properties, high-temperature stability, and wet-heat weight loss after diffusion modification.

[0043] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A process for preparing NdFeB magnets by controlling inorganic fluoride grain boundary diffusion using gallium-cobalt dual-element methods, characterized in that, Includes the following steps: S1. Perform surface pretreatment on sintered NdFeB magnets to obtain pretreated magnets; S2. Mix anhydrous neodymium fluoride powder and anhydrous praseodymium fluoride powder and dehydrate to obtain dehydrated inorganic fluoride powder; wherein the dehydrated inorganic fluoride powder is composed of 60-75wt% anhydrous neodymium fluoride powder and 25-40wt% anhydrous praseodymium fluoride powder. S3. Add gallium triacetylacetonate, anhydrous ethanol and ethyl acetate to the dehumidified inorganic fluoride powder obtained in step S2, and ball mill in an anhydrous system to obtain Ga-F interface-fixed intermediate slurry; the particle D50 of the Ga-F interface-fixed intermediate slurry is 0.55-0.90 μm; S4. Disperse anhydrous cobalt(II) acetylacetone in ethyl acetate to obtain a cobalt source dispersion. After step S3, add the cobalt source dispersion to the Ga-F interface fixation intermediate slurry and control the Co / Ga molar ratio to be 0.35-0.

65. After dispersion, a cobalt source post-confinement composite slurry is obtained. S5. Add polyvinyl butyral film-forming agent and non-aqueous polycarboxylate dispersant to the cobalt source confinement composite slurry obtained in step S4 to obtain a sequentially fixed composite diffusion source slurry. Coat the sequentially fixed composite diffusion source slurry onto the surface of the pretreated magnet obtained in step S1 and dry it to obtain a coated magnet. S6. Place the coated magnet obtained in step S5 in an inert atmosphere, first heat it at 210-240℃ for 25-45 min for oxygen-free pre-conversion before main diffusion, then heat it at 820-850℃ for 130-170 min for main grain boundary diffusion, and then perform segmented tempering to obtain a neodymium iron boron magnet modified by inorganic fluoride grain boundary diffusion regulated by gallium and cobalt dual elements.

2. The preparation process according to claim 1, characterized in that, In step S1, the sintered NdFeB magnet is an N48SH grade sintered NdFeB magnet; the surface pretreatment includes: lightly grinding the magnet surface to a surface roughness Ra of 0.6 μm, ultrasonically cleaning it in acetone and anhydrous ethanol for 3 min in sequence, and drying it at 80℃ and 100Pa for 20 min.

3. The preparation process according to claim 1, characterized in that, In step S2, the anhydrous neodymium fluoride powder and anhydrous praseodymium fluoride powder are dried at 120°C and 80 Pa for 2 hours, and then transferred to a ball mill container protected by dry argon gas after cooling.

4. The preparation process according to claim 1, characterized in that, In step S3, for every 12 parts by mass of the dehydrated inorganic fluoride powder, add 0.82-1.10 parts by mass of gallium triacetylacetonate, 24 parts by mass of anhydrous ethanol, 12 parts by mass of ethyl acetate and 60 parts by mass of zirconium oxide beads, and ball mill at 350 r / min for 1.4-3 h at 28 °C.

5. The preparation process according to claim 1, characterized in that, In step S4, for every 12 parts by mass of the dehydrated inorganic fluoride powder, 0.233-0.433 parts by mass of anhydrous cobalt(II) acetylacetonate are added.

6. The preparation process according to claim 1, characterized in that, In step S4, the cobalt source dispersion is added to the Ga-F interface fixation intermediate slurry within 5 minutes, and the stirring speed is maintained at 280 r / min during the addition. After the addition is completed, the dispersion continues for 40 minutes.

7. The preparation process according to claim 1, characterized in that, In step S5, the polyvinyl butyral film-forming agent is a 5.0% polyvinyl butyral solution, and the solvent of the polyvinyl butyral solution is composed of anhydrous ethanol and ethyl acetate in a mass ratio of 1:1; the solid content of the sequentially fixed composite diffusion source slurry is 21.3-21.8 wt%.

8. The preparation process according to claim 1, characterized in that, In step S5, the coating process includes: immersing the pretreated magnet in the sequentially fixed composite diffusion source slurry for 10 seconds at 25°C and 40% relative humidity, then removing it at 50 mm / min and allowing it to stand for 60 seconds; after drying, controlling the dry weight gain to be 3.75-3.85 mg / cm² based on the surface area of ​​the pretreated magnet. 2 .

9. The preparation process according to claim 1, characterized in that, In step S6, when performing the oxygen-free pre-conversion before the main diffusion, the oxygen content in the furnace is not higher than 30 ppm and the dew point is not higher than -45℃; the segmented tempering includes: after the main diffusion of the grain boundary is completed, cooling down to 540℃ and holding for 150 min, then cooling down to 430℃ and holding for 210 min.